Spatial spectrum of coherence signal for a defocused object images in digital holographic microscopy with partially spatially coherent illumination - Daria Klychkova; Vladimir Ryabukho (Компьютерная оптика, 2018)
We study the effect of a decrease in the magnitude of the coherence signal in high-frequency spatial spectrum for a defocused object image in transmission digital holographic microscopy with quasimonochromatic partially spatially coherent illumination. A theoretical description and results of the numerical simulation of the effect for a point scattering object are presented. The effect is experimentally studied by illuminating layered quasi-point scatterers with partially spatially coherent laser light obtained using a moving scatterer. The comparison of the experimental and theory-based numerical results shows them to be in good agreement.